A century of intervention in a Ramsar wetland – the case of the Coorong, Lower Lakes and Murray Mouth. Issue 2 (3rd April 2017) - Settre, Claire Maree; Wheeler, Sarah Ann
ABSTRACT: Coastal wetlands are among the more valuable ecosystems on the planet. Managing wetlands to maintain ecosystem function is physically and politically challenging, especially during drought. Management of the Coorong, Lower Lakes and Murray Mouth has been characterised by a sequence of active and reactive infrastructure interventions, first as active interventions to supply consumptive water demands and more recently as reactive emergency drought responses. However, infrastructure solutions are not necessarily synonymous with achieving sustainability. Infrastructure interventions have occurred at significant public expenditure and high opportunity cost. Greater attention to demand-based management strategies including time-limited environmental water acquisitions and state-based environmental water holdings provides an alternative to future infrastructure reliance. There is also considerable scope for greater provision of cultural flows and engagement with traditional owners to improve ecological condition.